THE ANALYSIS OF THE EDUCATORS’ ROLE TOWARDS THE ELEMENTARY SCHOOL STUDENTS’ LITERACY PROBLEM THROUGH THE HEUTAGOGY APPROACH - Abdul Halik; Rosdiah Salam; Rukayah Rukayah; Abd. Hafid (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2022)
The analysis of this study tries to observe the low literacy level of students in primary education, especially regarding the implementation of e-learning through the Belajar dari Rumah during the Covid-19 pandemic. This problem is assessed through a heutagogy approach. The analysis uses a diagnostic case study method with internet searching techniques. This diagnostic study is founded that educators' mastery of implementing LMS-based e-learning in hybrid (blended and flipped classroom) via interactive and integrative multimedia is a significant factor in providing interesting material with quality texts to increase elementary students' literacy. Optimizing e-learning through the heutagogy approach becomes the foundation for realizing independent learners as the vision of Merdeka Belajar. Thereby, the embodiment of Merdeka Belajar through heutagogy is an urgency in strengthening the educators’ quality, professionalism, and creativity to produce a Profil Pelajar Pancasila based on literacy level as one of its bases.